KRISIS POLITIK DI KALIMANTAN BARAT 1950: SUATU PROSES MENUJU INTEGRASI KE DALAM REPUBLIK INDONESIA - Mohammad Rikaz Prabowo; Aman Aman (Patanjala: Journal of Historical and Cultural Research, 2021)
This event was based on the background of competition between political groups after the recognition of Indonesian sovereignty on December 27, 1949, namely the pro-integration groups into the Republik of Indonesia through the West Kalimantan National Committee (KNKB), with those who wanted to maintain the status of the Special Region of West Kalimantan (DIKB) within the framework of a systemized Federal RIS. This competition resulted in a political crisis that affected the entire province. The republicans in the KNKB demanden the DIKB Government that West Kalimantan be part of the Republic of Indonesia. This desire was responded coldly, even though the DIKB figures rejected the entry of the TNI. This sparked demonstration that led to the arrest of republicans and a general strike which resulted in a political crisis. The political crisis subsided after the arrival of the RIS and DPR-RIS Commissioners. The arrest of Sultan Hamid II on April 5 1950 paralyzed DIKB and accelerated joining the Republic of Indonesia.